2015
DOI: 10.1128/jvi.03055-14
|View full text |Cite
|
Sign up to set email alerts
|

Rice Stripe Tenuivirus Nonstructural Protein 3 Hijacks the 26S Proteasome of the Small Brown Planthopper via Direct Interaction with Regulatory Particle Non-ATPase Subunit 3

Abstract: The ubiquitin/26S proteasome system plays a vital role in regulating host defenses against pathogens. Previous studies have highlighted different roles for the ubiquitin/26S proteasome in defense during virus infection in both mammals and plants, but their role in the vectors that transmit those viruses is still unclear. In this study, we determined that the 26S proteasome is present in the small brown planthopper (SBPH) (Laodelphgax striatellus) and has components similar to those in plants and mammals. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 64 publications
(95 reference statements)
4
36
0
Order By: Relevance
“…alienus , which can interact with WDV CP in both yeast two‐hybrid assay and pull‐down assay. This protein might involve in WDV spread in the tissues of leafhopper, because previous researches have showed that most viruses moved through the tissues of vector insects by directly binding to the vector's proteins (Huo, Liu, Zhang, Chen, & Li, ; Morin, Ghanim, Sobol, & Czosnek, ; Xu et al, ). For example, the specific interaction between viral nucleocapsid protein and sugar transporter 6 of Laodelphax striatellus is a key factor for determining whether the virus can invade midgut epithelial cells (Qin et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…alienus , which can interact with WDV CP in both yeast two‐hybrid assay and pull‐down assay. This protein might involve in WDV spread in the tissues of leafhopper, because previous researches have showed that most viruses moved through the tissues of vector insects by directly binding to the vector's proteins (Huo, Liu, Zhang, Chen, & Li, ; Morin, Ghanim, Sobol, & Czosnek, ; Xu et al, ). For example, the specific interaction between viral nucleocapsid protein and sugar transporter 6 of Laodelphax striatellus is a key factor for determining whether the virus can invade midgut epithelial cells (Qin et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In general, once orally acquired by its insect vector, a persistent circulative virus follows a sequential pathway, from ingestion through the stylet to gut to haemolymph and finally to the salivary glands (Jia et al, ; Liu et al, ). The successful spread of virions in the insect vectors requires specific interactions between the virus and vector components to overcome membrane barriers (Linz, Liu, Chougule, & Bonning, ; Rana et al, ) or prevent degradation by the vector's immune system (Gray et al, ; Liu et al, ; Xu et al, ). The virions are thought to hijack a host mechanism that most likely enables transport of essential macromolecules (Marsh & Helenius, ; Seddas et al, ; Wang, Wu, Liu, Wu, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these seven proteins, NS3 functions as a gene-silencing suppressor in plants and functions in the size-independent and noncooperative recognition of dsRNA [41,42]. A recent report demonstrated that RSV NS3 protein can hijack the 26S proteasome by interacting directly with the SBPH RPN3 protein [43]. Our observations using Y2H and GST pull-down assays confirmed that NS3 interacts with LsTUB (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…It has also been reported that the 26S proteasome plays a defensive role in protecting SBPH against RSV infection. The RSV p3 protein interacts with the RPN3 subunit of the 26S proteasome in SBPH and attenuates the host defense response by hijacking the 26S proteasome to facilitate viral replication [58]. We here demonstrate that the 26S proteasome functions in plants against RSV by targeting p3 for degradation, indicating that the interaction between the 26S proteasome and p3 differs between SBPH and plants (Fig 8).…”
Section: Plos Pathogensmentioning
confidence: 64%